STRENGTHENING THE AUTHORITY OF THE JUDICIAL COMMISSION IN UPHOLDING THE ETHICS OF JUDGES IN INDONESIA - Ghafur, Abd.; Rosmini, Rosmini; Tajali Nur, Insan (Al-Mubin, 2025)
This study aims to analyze the effectiveness of the authority of the Judicial Commission (KY) in the enforcement of the ethics of judges in Indonesia and propose an ideal construction to strengthen the authority of this institution. The KY, which is regulated by the 1945 Constitution and related laws, has an important role in maintaining the integrity of judges through supervision and recommendation of sanctions, but is constrained by limited authority that is limited to recommendations to the Supreme Court (MA), which is often not followed up. Through a doctrinal approach and qualitative analysis of primary, secondary, and tertiary data, this study examines the challenges faced by the KY in carrying out its duties, and offers a solution in the form of granting greater authority in imposing direct sanctions on judges who violate the code of ethics. This research is expected to make a theoretical and practical contribution in strengthening a clean and transparent judicial system in Indonesia